The multifaceted erdostein: facts on the desk. A review - Sergey L. Babak; Marina V. Gorbunova; Mariia A. Karnaushkina (ZAO "Consilium Medicum", 2024)
Erdostein is a mucoactive agent belonging to the group of thiol drugs with antioxidant, anti-inflammatory and antibacterial activity against a number of major respiratory pathogens. After transformation in the liver, erdostein is metabolized to a compound with an open ring M1 (MET-1) having unique properties. In the RESTORE study (2022), it was confirmed that erdostein significantly reduces the risks of severe exacerbations in patients with chronic obstructive pulmonary disease (COPD), reduces their duration, and reduces the number of hospitalizations with acute respiratory failure (ARF). The unique preventive properties of erdostein do not depend on the administration of inhaled (ICS) or systemic (SCS) corticosteroids to COPD patients, as well as on the level of eosinophilia in the blood. The results obtained contrast with the available therapy strategy, where thiol mucolytics are indicated in patients who do not use ICS-therapy and/or SCS-therapy. Moreover, this confirms the assumption about the use of erdostein in COPD patients as a drug for the phased withdrawal of ICS-therapy.